Pengaruh Religiusitas terhadap Kinerja Karyawan Muslim Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Pamekasan - Maulana, Haris; Fahrullah, A'rasy (Jurnal Ekonomika dan Bisnis Islam, 2020)
Optimizing the performance of a company is inseparable from the work achievement of the employees in carrying out all their duties. Religious factors become one of the factors driving the optimization of performance achievement wich must be maximized. This study aims to determine how the influencer of religiosity on the performance of muslim employees in the Regional Water Company (PDAM) Pamekasan. This research is quantitative study with a population of 48 employees in the Pamekasan Regency PDAM office, all of wich were used as reseach samples. Questionnaire is used as a data collection method using a likert scale as a measurement tool. Data analysis using simple linear regression analysis, partial test (T) and the coefficient of determination (R²) test using SPSS version 23. The result of simple linear regression analysis showed the regression coefficient was a 1 then employee performance has increased by 0,028. T test results are at a significance value of 0,828 > 0,05, wich means that the variable of religiosity does not affect employee performance. While the R² test result are at the value of 0,001, wich means that there are ither variables outside the study that affect the performance of PDAM Pamekasan employees.